Control Analysis of Stand-Alone Wind Power Supply System with Three Phase PWM Voltage Source Inverter and Boost Converter - Tin Zar Khaing; Lwin Za Kyin (Institute of Advanced Engineering and Science, 2015)
Wind power supply system is an effective, environmentally friendly power source for household and other applications. According to the wind speed changes in variation the output power of wind generator is not stable and constant. This paper proposes the variable speed stand-alone wind power supply system that includes Permanent Magnet Synchronous Generator, three phase diode rectifier, DC-DC boost converter, battery energy storage system, and voltage source inverter. DC-DC boost converter controls to extract maximum power from the available wind power. Battery energy storage system through bidirectional converter is to supply the load when wind power is shortage. To get the desired output voltage and frequency at the load side, the voltage source inverter with the sinusoidal pulse width modulation (SPWM) control technique has chosen. The harmonics generated from the VSI are filtered with simple passive LC filters. Simulation results of output voltages and currents, the total harmonic distortion (THD) are presented using MATLAB/Simulink.